The phosphate state and biochemical mobilization of phosphorus compounds in arboreal plants’ soils - Artyushenko, Olexandr; Dziuba, Oksana (Acta Agraria Debreceniensis, 2010)
Some indices of the phosphoric fractions of primery degraded soils, which are formed separate areas of technogenic landscapes, on a spoil-bank of iron-ore mine in the near of Kryvyi Rig, under act of lignosa, which are used for biological recultivation of degraded soils are investigated. Maintenance of mineral phosphates and features of organic phosphorus accumulation are set in soil under arboreal planting. Nutrient supply of plants is enhanced by mobile phosphates and their dynamics during vegetation period. Activity of alkaline and acid phosphatase enzymes are concerned also. On the basis of the soil enzymes activity information it is stated, that under the 35-years-old plantage of Robinia pseudoacacia L. the biochemical mineralization of organic phosphorus compounds passes considerably more actively than under Pinus pallasiana D.Don.